Speed Sensorless Motion Control Scheme for a Robotic Manipulator Under External Forces and Payload Changes - Jorge Pacheco; David Cortés-Vega; Hussain Alazki (Actuators)
This paper proposes the design of a speed sensorless robust discontinuous controller for the trajectory tracking problem of a 5-DOF robotic manipulator under payload changes and torque disturbances in the joints. The developed observer-based controller is capable of performing trajectory tracking, ensuring stability, fast error convergence and speed sensorless operation. In order to avoid joint speed measurement, an estimation scheme based on a differentiation algorithm is implemented to estimate it. Simulation tests developed in MATLAB/Simulink are presented to show the high performance of the proposed scheme for two different trajectories with the model of the CRS Catalyst-5 by Thermo Electron®, Burlington, ON, Canada.